2021
DOI: 10.35621/23587490.v8.n1.p120-135
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico De Gestantes Portadoras De Hiv/Aids No Brasil

Abstract: Objetivo: descrever o perfil epidemiológico de gestantes portadoras de HIV/Aids no Brasil. Metodologia: trata-se de uma revisão na literatura referente às gestantes portadoras de HIV/Aids. O levantamento bibliográfico foi realizado no mês de dezembro de 2019, utilizando as bases de dados Lilacs, Medline, SciELO e Google Acadêmico. Foram incluídos trabalhos completos, em português, publicados entre 2015 a 2019. Após avaliação, foram identificados 10 artigos que preencheram todos os critérios de inclusão e exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The epidemiological profile of the study participants showed a similar pattern of PLHIV in Brazil, with a higher prevalence of HIV/AIDS among males of white and brown color 3 . The differences found refer to age and sexual orientation or behavior from national data on PLHIV, which indicate that the highest frequency of PLHIV is observed in men who have sex with men 3 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The epidemiological profile of the study participants showed a similar pattern of PLHIV in Brazil, with a higher prevalence of HIV/AIDS among males of white and brown color 3 . The differences found refer to age and sexual orientation or behavior from national data on PLHIV, which indicate that the highest frequency of PLHIV is observed in men who have sex with men 3 .…”
Section: Discussionmentioning
confidence: 68%
“…In Brazil, 1,045,355 cases of HIV/AIDS have been reported between 1980 and June 2021. Between 2017 and 2021, an annual average of 36,800 new cases of HIV/AIDS has been reported in Brazil 3 . Regarding mental and psychiatric disorders, the occurrence of these disorders is 1.5-8 times higher in people living with HIV (PLHIV) than in the general or uninfected population 4 .…”
mentioning
confidence: 99%
“…Essa realidade já pode ser observada em Cascavel, como foi visto nos dados do presente estudo. Além disso, é importante ressaltar que um maior nível de escolaridade é fundamental para facilitar a procura por informações acerca da saúde, assim como um melhor entendimento sobre os procedimentos e tratamentos disponíveis para essas mulheres (Silva et al, 2021).…”
Section: Introductionunclassified

Hiv/Aids Em Gestantes No Brasil

Gurgel Fernandes Távora,
Ripardo Maranhão,
Menezes Dias
et al. 2024
Cadernos ESP